Cranioplasty using Polymethylmethacrylate (PMMA) self-curing by the conventional casting process: clinical case report - Jamil Elias DIB; Mario Serra FERREIRA; Matheus Branco Elias DIB; Wolney Ronaldo Abrahão SILVA; Ricardo Guimarães NEVES; Érica Miranda de TORRES; João Batista de SOUZA (Faculdade São Leopoldo Mandic, 2018)
Cranioencephalic trauma which results in extensive edema and / or bruising usually requires surgical treatment through a greater withdrawal of the bone portion. Thus, the absence of bone tissue implies the lack of protection of the brain tissue or even compromises the esthetics especially when located in the frontal or frontoparietal region. The purpose of this case report is to describe a treatment option for head trauma, through the prefabricated part by obtaining the skull model. These bone faults can be reconstructed either by the direct method using polymethylmethacrylate directly on the defects or by means of pre-made pieces such as prototyping or from the skull model. Although other techniques have many good points, some show certain drawbacks, from storage conditions below abdominal fat, preheating due to the release of heat during the high polymerization reaction or the high cost when they are prototyped. The technique described in this work reports its simple performance, eliminating the risk of local heating, allows prior sterilization in autoclave, it is biocompatible, allows perfect anatomical recovery, easy placement, low cost, also highlighs the advantage of the bucomaxillofacial surgeon's performance due to the familiarization with the relevant head and neck procedures. Clinical and tomographic examination after 24 months of treatment showed stability of the polymethylmethacrylate plate, adhesions to the bone margins, and absence of tissue alterations.